Impact of anti-fracture medications on bone material and strength properties: a systematic review and meta-analysis - Sharma, Shivani; Shankar, Vijay; Rajender, Singh; Mithal, Ambrish; Rao, Sudhaker D.; Chattopadhyay, Naibedya (Frontiers in Endocrinology, 2024)
Background and aims: Reduced bone mineral density (BMD) and micro-architectural deterioration contribute to increased fracture risk. Although the effects of anti-fracture medications (AFMs) on BMD are well-documented, their impact on bone material properties (BMP) remains poorly characterized. Accordingly, we conducted a systematic review and meta-analysis to evaluate the effects of AFMs on BMP. Based on data availability, we further categorized AFMs into anti-resorptives, bisphosphonates alone, and strontium ranelate subgroups to perform additional analyses of BMP in osteoporotic pateints.We did a comprehensive search of three databases, including PubMed, Web of Science, and Google Scholar, using various permutation combinations, and used comprehensive meta-analysis software to analyze the extracted data. Results: The 15 eligible studies (randomized and non-randomized) compared: 1) 301 AFMtreated patients with 225 on placebo; 2) 191 patients treated with anti-resorptives with 131 on placebo; 3) 86 bisphosphonate-treated patients with 66 on placebo; and 4) 84 strontium ranelate-treated patients with 70 on placebo. Pooled analysis showed that AFM significantly decreased cortical bone crystallinity [standardized difference in means (SDM) -1.394] and collagen-maturity [SDM -0.855], and collagen-maturity in cancellous bone [SDM -0.631]. Additionally, anti-resorptive (bisphosphonates and denosumab) significantly increased crystallinity [SDM 0.387], mineral-matrix ratio [SDM 0.771], microhardness [SDM 0.858] and contact hardness [SDM 0.952] of cortical bone. Anti-resorptives increased mineral-matrix ratio [SDM 0.543], microhardness [SDM 0.864] and decreased collagen-maturity [SDM -0.539] in cancellous bone. Restricted analysis of only bisphosphonate-treated studies, there was significant decrease only in collagen-maturity [SDM -0.650] in cancellous bone and increased in true hardness [SDM 1.277] in cortical bone. In strontium ranelate-treated patients, there was no difference in BMP compared to placebo.Collectively, our study suggests that AFMs improve bone quality, which explains their anti-fracture ability that is not fully accounted by increased BMD in osteoporosis patients.